Breeding cowpea for resistance to insect pests: attempted crosses between cowpea and Vigna vexillata - Fatokun, C.A. (2002)
Cowpea is grown mainly for its protein-rich grains, which is consumed in various forms in sub-Saharan Africa. Average grain yield in farmers' fields is generally low due to a number of biotic and abiotic stresses. The most important of the biotic stress factors causing extensive grain yield losses in cowpea are post flowering insect pests such as the legume pod borer and pod sucking bugs. Availability of varieties with resistance to these pests will be attractive to cowpea farmers as the crop could then be grown with less dependence on expensive, often adulterated chemicals that are not particularly environmentally friendly. To be able to develop such varieties, it is necessary that genes conferring resistance to these pests are available in the cowpea genome. Genes conferring resistance to these pests were found to exist in the genomes of some wild Vigna species such as V. vexillata and V. oblongifolia and efforts were made to transfer these genes from the wild Vigna sp. to cowpea. Pods were retained for up to seven days after pollination when V. vexillata lines served as female parents with cowpea. Embryos in pods resulting from these crosses did not develop beyond the globular stage. Several procedures aimed at overcoming this incompatibility were adopted without success. Among the techniques used to overcome incompatibility were in vitro culture of interspe cific hybrid embryos, hormonal treatments of flower buds prior to pollination, and polyploidization. No interspecific hybrids were obtained following the several attempts made, thus suggesting that very strong cross-incompatibility exists between cowpea and V. vexillata.